KONTRIBUSI KETERLIBATAN KARYAWAN DAN DESAIN PEKERJAAN TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR SERTA KINERJA ORGANISASI - ARIE AMBARWATI (STIE Indonesia Malang, 2019)
Organizational performance is the principal of subjects of who never used for discussion in the business world or the management of organization. Several factors and variables affecting organizational performance. This study attempts to analyze the contribution employees engagement, of the design to organization citizenship behavior (OCB) and organizational performance. Research methodology used is quantitative explanatory by using 55 respondents who was employees in the field of banking.Analysis of research suggests that there a connection directly or indirectly the contribution of the employees engagement, the design work against organization citizenship behavior ( OCB ) and organization performance. The analysis proved that only the employees engagement and organization citizenship behavior (OCB) that contributes significantly to direct and organizational performance, while the design work never contributes directly against the performance of the organization.Keywords: Employee engagement, Work desain, Organization Citizenship Organization, Organization performance.